Putting self-determination theory into practice: application of adaptive motivational principles in the exercise domain - Hancox, Jennie E.; Quested, Eleanor; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecile (Taylor & Francis, 2017)
Grounded in self-determination theory (SDT), and in the group exercise context, this qualitative study explored: (1) instructors’ experiences of operationalising motivational strategies following participation in an SDT-based training programme, (2) exercisers’ views on instructors use of motivational strategies and any impact on exercisers’ basic psychological needs and motivation and (3) the challenges and facilitators reported by instructors when implementing motivation strategies in practice. Thirteen indoor group cycling instructors and 15 exercisers, who had been regularly attending a group cycling class taught by one of the instructors, participated in semi-structured interviews. Ten instructors also completed self-reflective diaries detailing their experiences of implementing the need-supportive strategies. Data were analysed using the Framework Method and coding was performed using an abductive reasoning approach. Analysis revealed specific examples of ‘how to’ operationalise motivation strategies within group exercise settings. Challenges to implementation included: the structured nature of the group exercise class, initiating meaningful one-to-one conversations, phrasing instructions in a need-supportive way, and breaking old habits. Facilitators to implementation included establishing a connection with exercisers and understanding SDT. Findings are discussed in relation to the theoretical, practical and research implications. The findings of the present study could potentially be used to improve the design and training content of SDT-based training programmes in group exercise contexts and other similar group activity settings within sport and healthcare settings.